COSEISMIC RUPTURES AND TECTONIC LANDFORMS ALONG THE DüZCE SEGMENT OF THE NORTH ANATOLIAN FAULT ZONE (MS 7.1, NOVEMBER 1999) - Pucci S.; Palyvos N.; Pantosti D.; Barchi M.; Zabci C. (My University, 2006)
This paper presents a comparison between the pattern of surface ruptures produced by a single earthquake and patterns of cumulative deformation. We performed a detailed study of the 1999 earthquake coseismic ruptures and of the long-term tectonic landforms in a key area of the Düzce fault segment of the North Anatolian fault. We observed a scale-independent en echelon arrangement of the coseismic surface ruptures. As a whole, the long-term geomorphic expression of the Düzce Fault near the 1999 ruptures is evidence of the principal slip zone at depth that accommodates the bulk of the displacement during an individual rupture event. This may stay localized through many rupture episodes with persistent geometry and kinematics. The long-term tectonic and geomorphic expression of the fault in a broader area around the 1999 ruptures defines a wider deformation zone. In fact, an old and complex fault arrangement has been mapped, partially coinciding with the 1999 rupturing fault, suggesting that the 1999 ruptures are an incomplete expression of the long-term Düzce fault system. The relationships between the coseismic and the old fault systems suggest an evolution of the fault pattern trough time, with a tendency to simplify a geometric complexity into a straighter, mature trace. The integrated investigation of long-term tectonic morphologies and structural pattern offers a noteworthy frame to interpret the coseismic rupture kinematics and clarifies their complexities. Moreover, to fully understand the principal slip zone at depth, this work shows the importance of the study of strain distribution pattern and evolution of surface rupturing faults. Copyright 2006 by the American Geophysical Union.